KUALITAS HIDUP KLIEN TERAPI METADON DI PROGRAM TERAPI RUMATAN METADON (PTRM) SANDAT RSUP SANGLAH - Anggareni, Komang Tria; Diniari, Ni Ketut Sri (E-Jurnal Medika Udayana, 2017)
Quality of life is an important indicator of the success of a therapy. Methadone Maintenance Therapy (MMT) is one of the popular choices for drug substitution therapy. Aside from its role in harm reduction against HIV infection, MMT may potentially increase clients’ quality of life. This study aims to identify the quality of life of methadone therapy clients and its affecting factors. Descriptive study with cross sectional design was used to describe quality of life of clients at Program Terapi Rumatan Metadon (PTRM) Sandat RSUP Sanglah. Samples were taken by consecutive sampling technique. Quality of life parameters were measured through the WHOQOL-BREF questionnaires. Quality of life of 35 subjects, 48.6% is categorized to good, 51,4% is moderate, and 0% is poor. Clients in age group 11-40 yo (58.6%), well educated (85.7%), have a job (55.2%), not widower (56.6%), and have had therapy for less than 12 months (66.7%) are mainly have a good quality of life. Quality of life of methadone maintenance therapy clients showed moderate and good category with no significant difference and none of them in poor quality of life. For further researchesare expected to be a more in depth study of the four domains that affect quality of life and develop by method of correlation. . Keywords:quality of life, methadone therapy client, drug abuse